Controlled Source Audiofrequency Magnetotelluric method applied in urban area of Central Osaka, Japan (Journal of Nepal Geological Society, 2000)
A detailed study was carried out to find out the most suitable time for electromagnetic sounding in order to apply the CSAMT method in the urban area of Central Osaka. The preliminary data collected during the daytime were highly noise contaminated, which couldn't be attenuated even on increasing the sampling time. Because of this reason, all the soundings were obtained during the nighttime when the electromagnetic noises were drastically reduced. The changes in layer resistivities with depth, as obtained from the 1-D inversion of the observed data, correspond to the different reflectors as seen in the seismic section. It is found that the vicinity of Uemachi Fault, in the western part of the study area, is characterised by high conductivity.